The green children of Woolpit chronicles, fairies and facts in medieval England - Clark, John 1958- (University of Exeter Press, 2024)
This book introduces the story of the 'Green Children' and how it has been interpreted, retold, and reworked. Analysing the two accounts, and offering fresh translations from the Latin originals, it considers what the historians tell us happened, and then the children's own story of their homeland
Keywords: Grüne Kinder von Woolpit -- ca. 12. Jh.; Green children of Woolpit (Legendary characters); Woolpit (England) / Folklore